Erosion risk model for the Karlovassi basin (Samos Island - Eastern Aegean Sea, Greece). - Evelpidou, N.; Stamatakis, M. (Pan-European conference ‘Remote Sensing and Spatial Analysis Tools for Erosion Processes’, 2006)
The post-Alpine sedimentation history in Greece is mainly characterized by the development of terrestrial, marine and lacustrine successions. During the Upper Miocene salinity crisis marine evaporites, mainly gypsum, were formed in several basins across Greece (i.e. Ionian Islands, Crete Island). These evaporites present simple mineralogy and they are almost insoluble. As a result, they appeared to be quite resistant in weathering process and they are easily identified in the field. On the contrary, Upper Miocene evaporites of lacustrine origin have a more complicated mineralogy and they are rare in field outcrops in a worldwide scale, since they are commonly easily weathered. Even though, the adjacent to Aegean Sea, Western Anatolia volcanic terrain hosts a series of lacustrine evaporites, the only similar deposit in Greece is that of Karlovassi Basin, in Samos Island. The aim of the present paper is to study the erosion risk of the Upper Miocene evaporate - bearing formations of Karlovassi basin developing a GIS model based on Boolean logic. Some of the affecting parameters that were input into the model are: the vulnerability of the lithological formations, the run off model, the morphological slopes and the aspect, the tectonic discontinuities, the land use – land cover of the wider area and the man made intervention. The geographical distribution of the aforementioned parameters, along with their modelisation, resulted to an erosion risk map of the Karlovassi basin.